ANALISIS KESEHATAN PADA KOPERASI PONDOK PESANTREN AS-SAKINAH BOJONEGORO TAHUN BUKU 2011 DAN 2012 - Nurul Mazidah; Eka Siti Khomariyah (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2014)
This research is descriptive research. The population and`sample of this research is financial and non financial data of Pondok pesantren As-sakinah Bojonegoro 20011 and 2012. The sampling technique was not used in this research because this is population research. The data analysis technique that used is interview and documentation. This koperasi healthy analysis is based on regulation of kementrian UMKM RI no: 35.3/per/m.kukm/x/2007. There are eight aspects in scoring system: modal, productive activa quality, management, efficiency, liquidity, autonomy and growth, identity and obedience in syariah principle. From the total score gained can be identified based on healthy predicate. And the result showed that the score of Koperasi pondok pesantren As-sakinah Bojonegoro in 2011 is 69,25 and in 2012 is 76,17. From those findings it can be concluded that Koperasi Pondok pesantren As-sakinah Bojonegoro is quite healthy